A decomposition algorithm of fuzzy Petri net using an index function and incidence matrix. Issue 8 (15th May 2015) - Zhou, Kai-Qing; Zain, Azlan Mohd; Mo, Li-Ping
Highlights An index function to find out if the "OR" rule is presented. An FPN is divided into a set of sub-FPNs the proposed algorithm. A theorem is provided to compute the number of inference paths present in FPN.